Entrepreneurial intention among graduates of UiTM Perak Branch / Izmayani Sa’adin and Nursaadatun Nisak Ahmad - Sa’adin, Izmayani; Ahmad, Nursaadatun Nisak (2021)
Entrepreneurship has developed significantly in Malaysia recently. Thousands of students graduate from universities each year but only a small number of graduates are inspired to start up their own businesses. The objective of the study in general is to examine the intention to become entrepreneurs within the three domains particularly in the areas of personal attitude, perceived behavioural control and subjective norms. The study uses Ajzen Theory of Planned Behaviour to attain the said purpose. In gathering data, the questionnaire was based on the previous study conducted by Linan and Chen (2009). A total of 250 final year students participated in this study by using convenience sampling techniques. This study focused on fresh graduates who chose between working and becoming an entrepreneur after graduating. Personal attitude was identified as the most important area for dependent variable since the results showed a strong relationship with entrepreneurial intention, followed by perceived behaviour control. The outcomes also revealed that subjective norms showed a moderate relationship in correlation analysis. Therefore, future study should be carried out in order to understand the overall perspective of graduates in higher learning institutions